Implementasi Metode Fuzzy untuk Klasifikasi Tingkat Kesejahteraan Keluarga di Kecamatan Loura - Yunita Ngongo; Andreas Ariyanto Rangga; Alexander Adis (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
Achieving financial stability for the family is a goal that everyone has. The family is the most significant foundation for the growth of human life in Indonesia. The first and most important living environment where the personality that shapes a person's life is created is the family. The development of moral values, social justice, humanity, and religion is essentially a process decided by the family. The family is the first and main social structure that plays an important role in providing life values ​​to children who are growing and developing so that they can find purpose in their life journey. The classification of family welfare according to population data owned by the village government is the aim of this study. Based on the results of the study, fuzzy logic and the Tahani model can be used to process population data according to the level of family welfare, resulting in output in the form of family classifications such as prosperous, poor, and underprivileged families. To assess the effectiveness of incorporating fuzzy logic into the program being developed, the fuzzyTECH application is also used to test the program subdistrict.